Unraveling the role of cumulative triglyceride-total cholesterol-body weight index in stroke development: evidence from the CHARLS cohort - Luwen, Huang; Yunwei, Zhang; Lei, Xu; Linlin, Li; Ming, Yu (Frontiers in Medicine, 2025)
BackgroundThis study investigated the association between the cumulative triglyceride-total cholesterol-body weight index (TCBI) and the risk of stroke among middle-aged and older adults, focusing on hypertension as a potential mediator.MethodsData from 5,598 participants aged ≥ 45 years in the China Health and Retirement Longitudinal Study were analyzed over a median follow-up of 57.2 months. CumTCBI was calculated as ((TCBI(2011) + TCBI(2015))/2) × (2015–2011). The risk of stroke was the primary outcome. Cox proportional hazards models and restricted cubic splines were used to examine the association between CumTCBI and stroke risk. Mediation analysis investigated the role of hypertension as a potential mediator of the association between CumTCBI and stroke risk.ResultsDuring the follow-up period, 480 (8.93%) participants experienced stroke. The fully adjusted CumTCBI was significantly associated with stroke (HR per 1 SD = 1.166). A non-linearly association was observed, with stroke risk increasing when CumTCBI was below 12.639 (HR per 100 units = 1.166, P = 0.002) and remaining stable beyond this threshold (P = 0.356). Additionally, hypertension mediated 27.4% of the association.ConclusionCumTCBI is non-linearly associated with stroke risk, partially mediated by hypertension. Managing both metabolic status and hyperternsion may reduce stroke risk in aging populations.